Nursing Students’ Perceptions of Academic Literacy Education - Reflections from the Swedish Red Cross University - Stålberg, Anna (Journal of Academic Writing, 2023)
Academic literacies refer to academic writing as social practices. This study describes first-term nursing students’ perceptions of the academic literacy education provided and its significance for their forthcoming training and clinical practice. Nine student nurses at the Swedish Red Cross University participated in semi-structured interviews. Data were analysed using latent content analysis. Two categories were identified: A challenging but rewarding step focused on the students’ struggles to become academically literate. A professional outlook targeted the students’ perceptions of the requirement to acquire academic literacies for their training and future clinical practice. The results provide insights of dichotomous perspectives among nursing students regarding their need to acquire academic literacies. Some of the students convey a resistant and sceptical view of adding academic education to nursing training. Others acknowledge the requirement of being academically literate, a competence sometimes hard-won. However, in their struggles, teacher guidance was requested; an appeal that needs to be met with creative solutions. Repetitive approaches by teachers combined with the use of student initiatives are proposed to enable improved academic literacy levels among the students.